2013
DOI: 10.1371/journal.pone.0074300
|View full text |Cite|
|
Sign up to set email alerts
|

Hydronephrotic Urine in the Obstructed Kidney Promotes Urothelial Carcinoma Cell Proliferation, Migration, Invasion through the Activation of mTORC2-AKT and ERK Signaling Pathways

Abstract: Obstructive nephropathy is the most common presentation of urothelial carcinoma. The role of the urine in the obstructed kidney namely “hydronephrotic urine” in urothelial carcinoma has not been extensively explored. This study aims to evaluate whether hydronephrotic urine in the obstructed kidney could promote urothelial carcinoma. The hydronephrotic urine was collected from the obstructed kidneys of Sprague-Dawley rats induced by different periods of unilateral ureteral obstruction (UUO). By the inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Su CC reported that Tanshinone IIA inhibits the proliferation of human gastric cancer cells by G2/M phase arrest which results from inhibition of ERK [26]. Chang CH reported that hydronephrotic urine promotes urothelial carcinoma cell proliferation or migration through the activation of AKT and ERK signaling pathway to decrease the expression of p21 and p27 [40]. These results are similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…Su CC reported that Tanshinone IIA inhibits the proliferation of human gastric cancer cells by G2/M phase arrest which results from inhibition of ERK [26]. Chang CH reported that hydronephrotic urine promotes urothelial carcinoma cell proliferation or migration through the activation of AKT and ERK signaling pathway to decrease the expression of p21 and p27 [40]. These results are similar to our study.…”
Section: Discussionsupporting
confidence: 90%
“…The ERK signaling pathway was previously shown to participate in the progression and metastasis of lung cancer ( 38 ), where ERK1/2 phosphorylation can promote epithelial-to-mesenchymal transition and treatment resistance in lung cancer ( 39 ). ERK1/2 activity has been demonstrated to serve an important role in tumorigenesis by regulating a variety of biological processes, including apoptosis, proliferation and migration ( 40 , 41 ). The Bcl-2 family of proteins are central regulators of apoptosis, which are traditionally divided into two types, pro-apoptotic or anti-apoptotic, where Bcl-2 is the prototypic anti-apoptotic protein ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The progression of osteosarcoma is linked to the activation of many signaling pathways, one of which is MAPK, MEK and ERK1/2 signaling 21 . ERK1/2 activity plays an important role in tumorigenesis via the regulation of a variety of biologic processes, such as apoptosis, proliferation and migration through induction of the cyclin dependent kinase (CDK) inhibitors, including p21 and p27 22 23 24 . As our previous study 12 demonstrated, ERK1/2 played an important role in the development of osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%